Sustainable use of concrete aggregates in Argentina - Locati, Francisco (2011)
Córdoba province (Argentina) produces important quantities of aggregates, especiallyfor concrete structures. Low quality materials can decrease structure’s Ufe and increment environmental liabilities and the use of quartz- bearing rocks can develop alkali-silica reactions (ASR) which affect concrete durability. Rocks reactivityfrom Córdoba was evaluated through standardized methods showing good behaviour due to their favorable textural and microstructural characteristics.